MODAL SOSIAL PERAMU JAMU MADURA DALAM MEMBANGUN TRUST RELATION DENGAN PELANGGAN - Samsul Muarif; Ekna Satriyati (Universitas Trunojoyo Madura, 2023)
The making of Madurese herbs by herbalists and passing down the recipes to the next generation builds customer trust. Herbalists are independent and do not cooperate with other parties so that recipes are not copied by competitors. The herbalist also has a way to make the product always sell well in the market and have customers. Social capital is one of the parts that herbalists must have in running a traditional Madurese herbal medicine production business. This paper aims to provide information that social capital is a provision for herbalists to build a good image of their herbal brand. This is done so that the jamu brand can be widely recognized and has high trust (Trust Relationship) from customers to consume the jamu. The research location is in Bangkalan City. This research is a descriptive-analytic qualitative research using the unit of analysis of the community, namely those directly involved as herbalists and their customers. The results of the study are (1) Trust or trust is still one of the important factors for herbalists in running herbal medicine sales businesses in the wider community, (2) Relationships owned by herbalists can be used to establish good relationships in the form of cooperation with various parties needed, (3) Social capital obtained from building relationships and trust can have a positive impact on the sustainability of traditional herbal medicine businesses in Bangkalan.